2010
DOI: 10.2174/187152810792231869
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and Histamine Receptor Antagonists in Cancer Biology

Abstract: Histamine has been demonstrated to be involved in cell proliferation, embryonic development, and tumour growth. These various biological effects are mediated through the activation of specific histamine receptors (H1, H2, H3, and H4) that differ in their tissue expression patterns and functions. Although many in vitro and in vivo studies of the modulatory roles of histamine in tumour development and metastasis have been reported, the effect of histamine in the progression of some types of tumours remains contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 80 publications
2
43
0
Order By: Relevance
“…Histamine exerts its functions through binding to G protein-associated histamine H1, H2, H3, and H4 receptors (HRH1, HRH2, HRH3 and HRH4), resulting in the activation of different signal transduction pathways (31)(32)(33). In addition to the human HRH1, in the present study, we identified other HRH1 genes from other 13 vertebrate genomes and found that HRH1 exists in all types of vertebrates including the fish, amphibians, birds and mammals.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Histamine exerts its functions through binding to G protein-associated histamine H1, H2, H3, and H4 receptors (HRH1, HRH2, HRH3 and HRH4), resulting in the activation of different signal transduction pathways (31)(32)(33). In addition to the human HRH1, in the present study, we identified other HRH1 genes from other 13 vertebrate genomes and found that HRH1 exists in all types of vertebrates including the fish, amphibians, birds and mammals.…”
Section: Discussionmentioning
confidence: 61%
“…A large number of molecules involved in cell proliferation and key events in tumor development and progression have been extensively investigated including histamine (31)(32)(33). Histamine exerts its functions through binding to G protein-associated histamine H1, H2, H3, and H4 receptors (HRH1, HRH2, HRH3 and HRH4), resulting in the activation of different signal transduction pathways (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, H 2 R antagonists stimulated melanogenesis and inhibited proliferation in B16-C3 mouse melanoma cells (Uçar, 1991). It was also found that melanoma tumour growth was not modulated by in vivo histamine treatment while treatment with terfenadine, an H 1 R antagonist, in vitro induced melanoma cell death by apoptosis and in vivo significantly inhibited tumour growth in murine models (Blaya et al, 2010). Differences between melanoma cells in their capacity to produce and degrade histamine could explain the different sensitivities of melanoma cell types to exogenous histamine treatment.…”
Section: Histamine Receptors In Melanomamentioning
confidence: 95%
“…Besides this chemotactic action in immune cells it has also been reported that histamine promotes invasiveness specifically through activation of H1 receptor in human cytotrophoblasts required to initiate blastocyst implantation (Liu et al, 2004). Regarding tumor cells it has been reported that histamine acts as a chemoattractant for human carcinoma and melanoma cells via H1 receptor stimulation (Blaya et al, 2010;Tilly et al, 1990). Accordingly, the antiallergic compound tranilast inhibits cell migration and invasion in human malignant glioma cells blocking H1 receptors (Platten et al, 2001).…”
Section: Histamine and Histamine Agonists Modulate Mda-mb 231 Cells Mmentioning
confidence: 99%
“…It is well known that diverse tumoral tissues and cell lines express the different histamine receptors through which histamine brings about its effects on cell proliferation, differentiation, survival and death. A great deal of evidence shows a relevant role of histamine in tumor progression, however controversial results are published depending on the cell type and the histamine receptor subtype that is activated (Blaya et al, 2010;Francis et al, 2009;Parsons & Ganellin, 2006;Soule et al, 2010). It has also been determined that numerous tumour tissues and cell lines express L-histidine decarboxylase, the histamine-synthesizing enzyme, and contain high levels of endogenous histamine which released to the extracellular media may exert its effects via a paracrine or autocrine regulation Pós et al, 2004;Rivera et al, 2000).…”
Section: Introductionmentioning
confidence: 99%